Emerging Issues of data breach and need of Cybersecurity (International Journal of Food and Nutritional Sciences, 2022)
This research paper delves into the landscape of cybersecurity awareness and challenges among small and medium-sized enterprises (SMEs), shedding light on their preparedness in navigating the intricate realm of digital security. Employing a quantitative approach, we assessed the level of cybersecurity awareness and explored the various challenges faced by SMEs in dealing with issues related to cyber threats. Our findings reveal a substantial level of cybersecurity awareness among SMEs, with participants demonstrating familiarity with common threats, preventive measures, and the significance of cybersecurity. However, the study also underscores the multifaceted challenges that SMEs encounter, including budget constraints, training deficiencies, rapid threat evolution, employee awareness gaps, and compliance complexities. The implications of these findings extend to policymakers, practitioners, and technology providers, offering actionable insights to enhance SMEs' cybersecurity resilience. As the digital landscape continues to evolve, fostering a culture of cybersecurity within SMEs emerges as a critical imperative for sustainable growth and safeguarding digital assets.